Post-traumatic arthritis: overview on pathogenic mechanisms and role of inflammation. Issue 2 (6th September 2016) - Punzi, Leonardo; Galozzi, Paola; Luisetto, Roberto; Favero, Marta; Ramonda, Roberta; Oliviero, Francesca; Scanu, Anna
Abstract : Post-traumatic arthritis (PTA) develops after an acute direct trauma to the joints. PTA causes about 12% of all osteoarthritis cases, and a history of physical trauma may also be found in patients with chronic inflammatory arthritis. Symptoms include swelling, synovial effusion, pain and sometimes intra-articular bleeding. Usually, PTA recoveries spontaneously, but the persistence of symptoms after 6 months may be considered pathological and so-called chronic PTA. A variety of molecular, mechanobiological and cellular events involved in the pathogenesis and the progression of PTA have been identified. The activation of inflammatory mechanisms during the PTA acute phase appears to play a critical role in the chronic disease onset. Human studies and experimental models have revealed that a series of inflammatory mediators are released in synovial fluid immediately after the joint trauma. These molecules have been proposed as markers of disease and as a potential target for the development of specific and preventative interventions. Currently, chronic PTA cannot be prevented, although a large number of agents have been tested in preclinical studies. Given the relevance of inflammatory reaction, anticytokines therapy, in particular the inhibition of interleukin 1 (IL-1), seems to be the most promising strategy. At the present time, intra-articular injection of IL-1 receptor antagonist is the only anticytokine approach that has been used in a human study of PTA. Despite the fact that knowledge in this area has increased in the past years, the identification of more specific disease markers and new therapeutic opportunities are needed.